2020
DOI: 10.3390/ijms21176207
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Fusobacterium Species in Oral Cancer Progression: A Literature Review Including Other Types of Cancer

Abstract: Chronic inflammation caused by infections has been suggested to be one of the most important cause of cancers. It has recently been shown that there is correlation between intestinal bacteria and cancer development including metastasis. As over 700 bacterial species exist in an oral cavity, it has been concerning that bacterial infection may cause oral cancer. However, the role of bacteria regarding tumorigenesis of oral cancer remains unclear. Several papers have shown that Fusobacterium species deriving the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 68 publications
(83 reference statements)
1
36
0
Order By: Relevance
“…At the species level, we confirmed that F. naviforme , P. stomatis , and N. flavescens were significantly enriched in TT. F. naviforme is known to be associated with the development and progression of OSCC ( Fujiwara et al, 2020 ). Two reports have indicated that the abundance of P. stomatis is significantly higher in TT than in NPT ( Pushalkar et al, 2012 ; Zhang L. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the species level, we confirmed that F. naviforme , P. stomatis , and N. flavescens were significantly enriched in TT. F. naviforme is known to be associated with the development and progression of OSCC ( Fujiwara et al, 2020 ). Two reports have indicated that the abundance of P. stomatis is significantly higher in TT than in NPT ( Pushalkar et al, 2012 ; Zhang L. et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a variety of pathogenic microorganisms can cause long-term colonization in tumor cells by reshaping the host immune microenvironment, leading to tumor immune escape and promoting malignant progression [28]. For F. nucleatum, one of the most virulent oral pathogenic bacteria [29], its endotoxin can suppress the body's immune response, thus colonizing the body for a long time and promoting the malignant progression of many tumors, such as oral squamous and esophageal squamous cancers and colon cancer [30].…”
Section: Discussionmentioning
confidence: 99%
“…If the DNA damage in F. nucleatum -infected cells is so severe that the levels of the Ku70 protein are too low to ensure efficient DNA repair, the severely defective DNA is not repaired in a timely manner and abnormal proliferation of OSCC cells can occur. Nevertheless, the detailed mechanism of the interplay between F. nucleatum and Ku70 remains unclear [ 29 , 73 ].…”
Section: Oral Bacteria Associated With Oral Cancermentioning
confidence: 99%